RR Lyrae stars in stellar streams with Gaia: the escapers - Abbas, Mohamad; Grebel, Eva K.; Simunovic, Mirko (The astrophysical journal, 2021)
We attempt to identify RR Lyrae (RRL) stars in stellar streams that might have escaped from seven globular clusters (GCs) based on proper motions, distances, color-magnitude diagrams, and other properties extracted from the Gaia Early Data Release 3 (EDR3) database. Specifically, we cross-match two large RRL stars catalogs (from Gaia DR2 and Catalina Sky Survey) with each other and with the EDR3 database, and we end up with a sample of ∼150,000 unique RRL stars. We calculate distances to RRL stars using the M G -[Fe/H] and M V -[Fe/H] absolute magnitude-metallicity relations and adopt [Fe/H] values for the GCs from different spectroscopic studies. We also constrain our search to areas where stellar streams associated with GCs were previously suggested or identified in other studies. We identify 24 RRL stars that might have escaped from the following seven GCs: Palomar 13 (Pal 13), NGC 6341 (M92), NGC 5904 (M5), NGC 5466, NGC 1261, NGC 288, and NGC 1851. We list our findings in Table 2.
Gesehen am 18.08.2021